Blood-based AT(N) biomarkers for Alzheimer s disease and frontotemporal lobar degeneration in Latin America - Garcia-Serrano, A (SPRINGERNATURE, 2026)
Dementia diagnosis increasingly relies on blood-based biomarkers, yet their performance in diverse populations remains insufficiently characterized. Latin America, with substantial genetic and environmental heterogeneity, is particularly underrepresented in biomarker research. Here we show that plasma AT(N) biomarkers can distinguish Alzheimer s disease (AD) and frontotemporal lobar degeneration (FTLD) in a multinational Latin American cohort (N = 605). A beta 42/A beta 40 amyloid-beta ratios were reduced and levels of phosphorylated tau (p-tau217, p-tau181) and neurofilament light chain (NfL) were elevated in both disorders, with NfL showing greater increases in FTLD. Classification models achieved receiver operating characteristic areas under the curve (ROC AUCs) of 83% for AD and 88% for FTLD. Meta-analyses confirmed consistency across countries, and these markers correlated with executive, memory and global cognitive impairment. Biomarker alterations combined with disease-specific neuroimaging patterns and cognitive measures further improved accuracy (ROC AUCs of 89% for AD and 95% for FTLD). These findings indicate that plasma AT(N) biomarkers, combined with neuroimaging and clinical assessments, can enhance dementia diagnosis across diverse Latin American populations.